1975
DOI: 10.1136/hrt.37.7.684
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic mitral systolic motion in left ventricular aneurysm.

Abstract: An abnormal, convex systolic anterior motion of the mitral valve, somewhat similar to that seen in idiopathic hypertrophic subaortic stenosis (hypertrophic obstructive cardiomyopathy) and occasionally in atrial septal defect, was found on the echocardiogram in 8 out of 9 patients with angiographically (7 patients) and/or clinically (2 patients) diagnosed left ventricular aneurysm secondary to myocardial infarction. The only patient whose echocardiogram failed to demonstrate convex systolic anterior motion was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Isovolumic left ventricular shape changes have previously been studied angiographically, and have been described in normal subjects, and in patients with prolapsing mitral valve cusp (Gooch et al, 1972) or ischaemic heart disease. They have previously not been detected by echocardiography, though an abnormality of systolic mitral motion described by Greenwald et al (1975) may be explicable on the basis of mitral valve opening being late when compared with the onset of posterior movement of the mitral ring or posterior left ventricular wall.…”
Section: Discussionmentioning
confidence: 92%
“…Isovolumic left ventricular shape changes have previously been studied angiographically, and have been described in normal subjects, and in patients with prolapsing mitral valve cusp (Gooch et al, 1972) or ischaemic heart disease. They have previously not been detected by echocardiography, though an abnormality of systolic mitral motion described by Greenwald et al (1975) may be explicable on the basis of mitral valve opening being late when compared with the onset of posterior movement of the mitral ring or posterior left ventricular wall.…”
Section: Discussionmentioning
confidence: 92%
“…Another significant factor in the genesis of SAM may be the vigorous contraction of the LVPW (1,3,6,7,9,29). This vigorous contraction of the LVPW may occur as part of the generalized hyper contractile state as in volume overload of the left ventricle (aortic or mitral regurgitation) or as compensatory hypercontractility of the LVPW due to paradoxic septal motion as in atrial septal defect (7) or aneurysm of the anteroseptal wall of the left ventricle (8). Greenwald et al (8) observed SAM without ASH in patients with aneurysm of the left ventricular anterior wall and apex but not in a patient with aneurysm of the LVPW.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Come et al (3) have proposed that the hypercontractile state of the left ventricular myocardium may be responsible for the production of SAM in the absence of ASH. Exaggerated left ventricular posterior wall (LVPW) motion has been implicated in the production of SAM in atrial septal defect (7) and in aneurysm of the left ventricular anterior wall (8). Gehrke and Goodwin (9) in a recent report have proposed that in patients with IHSS also, it is the vigorous LVPW motion that is responsible for SAM (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…M-mode echocardiographic studies have shown that SAM apparently involving the anterior mitral leaflet may occur in other conditions and, like asymmetric septal hypertrophy, does not appear to be specific to hypertrophic cardiomyopathy (Goodman er al., 1979;Greenwald et al, 1975;Nanda et al, 1975Nanda et al, , 1977Pearlman et al, 1979).…”
Section: Left Ventricular Outflow Obstructionmentioning
confidence: 99%